Students’ Academic Integrity Index in Using Generative Artificial Intelligent among Islamic Education Major Students in Islamic Higher Education - Zalisman, Zalisman (POTENSIA: Jurnal Kependidikan Islam, 2023)
This study examines the academic integrity of Islamic education students in their utilization of generative artificial intelligence (GenAI) techniques. Data were gathered from 385 students utilizing a survey study methodology at three Islamic higher education institutions in Riau Province, Indonesia: Islamic University of Riau, Al-Kifayah Riau Islamic College, and Diniyyah Riau Islamic Institute. These institutions serve as pivotal centers for the amalgamation of Islamic beliefs with modern academic procedures. Data were collected utilizing a standardized questionnaire derived from the Jisc Digital Capability Framework, concentrating on students' ethical awareness, plagiarism, citation practices, and responsible AI utilization. An incidental sampling method was utilized, and the survey was conducted using Google Forms. The results indicate a diverse comprehension of the facets of academic honesty. Students exhibited elevated levels of comprehension of academic ethics (40% high) and Islamic values (50% medium). Nevertheless, diminished levels were noted in domains such as plagiarism (45% deficient), adherence to regulations (40% deficient), and prudent AI utilization (35% deficient), signifying deficiencies in ethical digital literacy. These findings underscore the necessity for educational approaches that amalgamate AI knowledge with Islamic ethical principles. Enhancing academic integrity necessitates specific policies and instruction in digital ethics to guarantee that AI facilitates learning instead of compromising academic honestyTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//